The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15171/jcvtr.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ramadan Fasting on Serum Amyloid A and Protein Carbonyl Group Levels in Patients With Cardiovascular Diseases

Abstract: Introduction: Serum amyloid-A (SAA) and protein carbonyl group are rigorously related with cardiovascular diseases (CVDs) as a sensitive marker of an acute inflammatory state and as an important index of oxidative stress, respectively. Moreover, diet is one of the main factors that can modify cardiovascular risks. Therefore, this study aimed to investigate the effects of Ramadan fasting on SAA and protein carbonyl group levels in patients with CVDs. Methods: Twenty-one patients (21 male; mean age 52±9 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A total of 416 proteins were identified as AMI preferably accumulated proteins, of which 76 were MI-3d special, 210 were MI-7d special, and 120 were increased at both 3 and 7 days after AMI (Figure 2 , Supplementary Tables 3 – 6 ). Several proteins in our list of DAPs have been reported to be crucial for AMI or left ventricular remodeling, including serum amyloid A protein (SAA) [ 26 ], S100 calcium binding protein A (S100A) [ 27 ], galectin [ 28 ], alpha-2-macroglobulin (A2M) [ 29 ], and cathepsin S [ 30 ]. Nevertheless, new candidates involved in the molecular changes after AMI might be identified by further examination of these data.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 416 proteins were identified as AMI preferably accumulated proteins, of which 76 were MI-3d special, 210 were MI-7d special, and 120 were increased at both 3 and 7 days after AMI (Figure 2 , Supplementary Tables 3 – 6 ). Several proteins in our list of DAPs have been reported to be crucial for AMI or left ventricular remodeling, including serum amyloid A protein (SAA) [ 26 ], S100 calcium binding protein A (S100A) [ 27 ], galectin [ 28 ], alpha-2-macroglobulin (A2M) [ 29 ], and cathepsin S [ 30 ]. Nevertheless, new candidates involved in the molecular changes after AMI might be identified by further examination of these data.…”
Section: Discussionmentioning
confidence: 99%
“…Ramadan fasting has also been shown to have some beneficial effects on endothelial function, like improved nitric oxide availability, which can affect cardiometabolic risk [ 158 ]. Some studies investigated the effect of Ramadan fasting on inflammatory markers and showed that there was a significant reduction in CRP levels, the attenuation of proinflammatory cytokines, a decrease in IGF-1 and IL-2 levels, an increase in adiponectin, a decrease in TNF-α and a reduction of serum amyloid A and protein carbonyl group levels [ 159 , 160 , 161 , 162 , 163 ]. However, the effects are not conclusive and an improvement in cardiometabolic risk factors cannot be substantiated by current studies due to several limitations.…”
Section: Metabolic Parametersmentioning
confidence: 99%
“…In normal healthy humans without a cardiovascular risk, fasting could help to decrease the inflammation biomarker (IL-1, IL-6, TNF-α) (Faris et al, 2019), oxidative stress (malondialdehyde) (Faris et al, 2019), body weight (Kul et al, 2013), waist circumstance (Sayedda et al, 2013), fasting blood glucose (Kul et al, 2013), LDL (Kul et al, 2013), trygliceride (Ganesan et al, 2018) and blood pressure (Id et al, 2019). In humans with a risk of or with cardiovascular disease, fasting could help to decrease their body weight (Salahuddin et al, 2014), body mass index (Wei et al, 2017), body fat percentage (Wei et al, 2017), blood pressure (Salahuddin et al, 2014), triglyceride (Iso et al, 2014), the biomarker of inflammation (serum amyloid A) (Asadi et al, 2015), the biomarker of oxidative stress (protein carbonyl) (Asadi et al, 2015) and the biomarker of endothelial dysfunction (asymmetric dimethylarginine) (Youse et al, 2014) while increasing the vascular endothelial growth factor (VEGF) (Youse et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Fasting Benefits in Blood Pressure (Trepanowski et al, 2017) Increased HDL Akaberi et al (Akaberi, Golshan, Moojdekanlo, & Hashemian, 2014) Improved HDL, LDL/HDL ratio, TG/HDL ratio Kul et al (Kul et al, 2013) Decreased body weight, fasting blood glucose and LDL at people healthy Faris et al (Faris et al, 2019) Decreased biomarkers of inflammation (IL-1, IL-6, TNF-α) and decreased oxidative stress malondialdehyde (MDA). Salahuddin et al (Salahuddin et al, 2014) Can be used as complementary treatment for reducing blood pressure and body weight in people with hypertension Mazurak et al (Mazurak & Gu, 2013) Decreased body weight and cortisol diurnal profil Iso et al (Iso et al, 2014) Decreased trygliceride Asadi et al (Asadi et al, 2015) Decreased biomarkers of inflammation (serum Amyloid A and protein carbonyl) Radhakishun et al (Radhakishun, Blokhuis, Vliet, & Rosenstiel, 2014) Decreased percentage of fat Horne et al (Horne et al, 2018) Improved body weight and lower prevalence of cardiovascular disease Sayedda et al (Sayedda, Kamal, & Ahmed, 2013) Decreased body weight, waist circumference and mean blood pressure (healthy)…”
Section: Fasting Benefits For Body Weight Maintainingmentioning
confidence: 99%